Identifying Students’ Learning Styles in English Learning - Zahirah M, Nur Fadilah; Muhayyang, Maemuna; Aeni, Nur (State University of Makassar, 2024)
This research highlights students’ learning styles in English learnin to find out (1) the types of learning styles of class VIII students at SMP Negeri 24 Makassar, and (2) how do class VII students at SMP Negeri 24 Makassar empower their learning styles in English learning. This research used mixed methods taking 118 class VIII students of SMP Negeri 24 Makassar as the sample by using random sampling techniques. The instruments were questionnaire, observation, and interview. Twenty-five students as representatives of the three types of learning styles were observed and interviewed regarding how they empowered their learning styles. The results show that (1) class VIII students of SMP Negeri 24 Makassar predominantly have a visual learning style with a total of 66 students (55.93%), followed by the auditory learning style of 43 students (36.44%), and kinesthetic learning style of 9 students (7.63 %), and (2) visual learning style students empower their learning style by having neat and orderly writing, note important points from the material, and utilize online media; auditory learning style students empower their learning style by collaborate in doing their assignments, create a calm environment, and utilize online media; and kinesthetic learning style students empower their learning style by point to the text while reading, choose practical activities, and move their body parts when they are focused. Thus, it can be concluded that class VIII students at SMP Negeri 24 Makassar predominantly have visual learning style by empowering their learning style with activities that rely on their sight, while students with auditory learning style rely on their hearing and students with kinesthetic learning style are happy with activities that rely on physicality.Key words– visual, auditory, kinesthetic, learning styles, English learning.